Efek Pupuk Bio-Kimia Realstrong Dan Pupuk Kandang Pada Pertumbuhan Dan Hasil Beta vulgaris L - Donatus Dahang; Sri Desi Br. Sinuhaji (JURNAL AGROTEKNOSAINS, 2019)
The research on effect of manures and biochemical RealStrong fertilizer had been done. The research was conducted at Aji BuharaVillage, Tigapanah Sub- district,Karo Regency,North Sumatra, February to April 2018.The proposed of the study was to see the effects of the fertilizers in growing and producing of Beta vulgaris. Random cluster block design with factorial classic was applied,factor 1; manures: P0: control, P1:chicken’s manures 1, 5 kg/plot, andP2:caw’s manures 1, 5 kg/plot. Factor 2, Biochemical RealStrong fertilizers: R0= control,R1 = 125gr/plot, R2 = 250gr/ plotandR3= 375gr/plot. Results of the study shown that the effect of P1 had given a highest growing i.e 33.88 cm and(R3)34.90 cm. Kinds and dosage of the fertilizers also influence of productions of the plant. The manure P1 had given production to 101.64 g/sampeland biochemical Realstrong R3given production of 3.20 kg/plot